Perbedaan Abnormal Return Perusahaan Sebelum, Pada Saat, dan Sesudah Pengumuman Annual Report Award - Siska, Adilla Juita (Jurnal Ekonomi, 2012)
Annual report awars affect the return of the company, in order to obtain an indication that companies are implementing GCG well responded by the market that investors. This research aimed to obtain the differences of abnormal return by before, at the time, and after annual report award of announcement period. Sampling was done in purposive sampling, which is a sampling based on a common characteristic that is inherent in a sample, the goal is to specialize which companies deserve the ARA Award. Before perfoming the hypothesis testing conducted prior to normality test. Normality testing was intended to see whether the sample data are normally distributed or not. Normality testing was conducted using one sample kolmogorov-smirnov test contained in the SPSS program. The hypothesis to be tested in this study using the event study with paired sample t-test. The result shows that abnormal return differences between befors and during also after the announcement of ARA. This research recomended that market adjusted model must be choise by return estimated with market index.